Modified sorbents based on natural mineral and its mechanical properties - Kenzhalievich, Kenzhaliyev Bagdaulet; Tatiana, Surkova; Dossymbayeva, Zamzagul; Kairgeldyevna, Koizhanova Aigul; Dinara, Yessimova; Bekzat, Abdikerim (Jurnal Pendidikan Teknologi Kejuruan, 2024)
The use of modified sorbents based on natural minerals, widely distributed in Kazakhstan, is a promising direction. This direction is related to the development of domestic ion-exchange materials. The republic lacks its own production of synthetic sorbents. The environmental situation in the regions of uranium ore mining and processing is also important. Moreover, the application of synthetic sorbents is not always justified due to their high cost, while the use of natural sorbents is limited by their low sorption capacity. The development of modified ion-exchange materials based on a combination of these is a pressing issue for various industries. Research has been conducted on the choice of modification methods for natural sorbents and the evaluation of their sorption capacity after modification. The modification of natural minerals zeolite and shungite using the "solid-phase extractants" method was carried out in two stages. At the first stage, the modification was performed with organic extractants and compositions based on them, and at the second stage with phosphoric acid in combination with polyacrylamide. The natural sorbents used were zeolite from the Kusmuryn deposit and shungite from the Koksu deposit, following preliminary flotation. The mechanical strength of sorbents modified by different methods was compared with the original ion-exchange materials. Studies of the sorption process have shown that the best results for uranium sorption were obtained with modified sorbents: zeolite modified with a mixture of extractants Di-2-Ethylhexyl phosphoric acid (Di-2-EHPA), Tributyl phosphate (TBP), kerosene, and shungite modified with phosphoric acid in the presence of Polyacrylamide (PAA).